Multi-objective optimizing spring placement and stiffness in slider-crank mechanisms for enhanced dynamic parameters - Hoang Minh Dang; Van Binh Phung; Van Thanh Tien Nguyen (PLoS ONE, 2025)
The slider-crank mechanism (SCM) is fundamental to various mechanical systems. However, optimizing its dynamic performance remains a pressing challenge due to excessive torque, joint reactions, and energy consumption. This study introduces two key innovations to address these challenges: (1) the integration of springs into SCM to optimize dynamic performance and (2) a novel hybrid optimization approach combining the Conjugate Direction with Orthogonal Shift (CDOS) method and Parameter Space Investigation (PSI). The mathematical model evaluates the effects of spring placement and stiffness on critical performance parameters such as energy efficiency, torque demands, and joint forces. The hybrid CDOS-PSI approach systematically identifies optimal design configurations to balance these performance objectives. The methodology’s efficacy is validated through a case study on a wood splitter, a commonly used agricultural and industrial machine. Experimental tests were carried out to measure splitting forces for different wood types, enabling accurate model calibration. Results demonstrate that the spring-integrated SCM reduces dynamic loads significantly compared to conventional designs. Comparative numerical analysis confirms the proposed model’s accuracy, with less than 5% deviations. This research offers innovative contributions to SCM design by combining spring-based dynamic enhancement with a novel hybrid optimization framework for improved efficiency and durability in practical applications.